Aplikasi Reharmonisasi lagu Silent Night dan Joy To The World untuk Pembelajaran Piano bagi Remaja di Gereja Pantekosta Hagios Family Yogyakarta - SISKA EUNIKE BUTAR-BUTAR (Saraswati)
Reharmonization Application of Silent Night dan Joy To The World in Piano Learning for the accompanist of the youth worship music in the Pentecostal Church of Hagios Family Yogyakarta. The harmony elements application through the songs: Joy to the Lord and Silent Night become a breakthrough in a piano learning for the accompanist of the youth worship music in the Pentecostal Church of Hagios Family Yogyakarta. Both songs have been reharmonizationed for Christmas and before Christmas, so it becomes very familiar in the ears of Christians worship music accompaniment especially the youth in the church. It is very effective to improve the harmonization ability because many of the harmony processing that more progressive such as diminished chords, augmented chords, chord substitutions, slash chords, chord suspension, extension chords and addition chords applied in these songs. Through the learning of piano, youth can be familiar in knowing the term of chords and its progression that can be applied in songs of worship. In addition, it makes the song more varied, not monotonous and provides different shades. Key words: Reharmonization, learning